A comprehensive study of enzyme-treated soy protein on intestinal barrier integrity, inflammatory responses, and liver lipid metabolism in Micropterus salmoides - Ju Zhao; Quanquan Cao; Min Jin; Tingwen Shen; Laia Ribas; Haifeng Liu; Jun Jiang (Journal of Agriculture and Food Research)
A 13 weeks feeding assessment was performed with the aim of determining the influence of enzyme-treated soy protein (ETSP) supplementation on growth performance, intestinal barrier function, liver lipid metabolism and related signaling pathways of largemouth bass (Micropterus salmoides). A total of 1000 largemouth bass (initial average weight: 22.3 ± 0.1 g) were fed five different diets used in the experiment, each with a different amount of ETSP: 0.0 (M1), 20.0 (M2), 40.0 (M3), 60.0 (M4), and 80.0 (M5) g/kg. The results demonstrated that dietary ETSP supplementation significantly improved growth performance, body composition, and nutrient retention (P<0.05). Histological examination revealed significantly greater intestinal villus height in fish fed optimal ETSP levels (P<0.05). The 40.0 g/kg ETSP diet enhanced intestinal barrier function by upregulating tight junction proteins and anti-inflammatory cytokines while downregulating pro-inflammatory factors through modulation of the AMPK-SIRT1-NF-κB signaling pathway (P<0.05). Moreover, histological examination revealed optimal ETSP (40.0 g/kg) improved hepatic macrovesicular steatosis and cellular nuclei displacement, restrain lipid vacuoles' relative area, also activities of plasma alanine aminotransferase (ALT) and aspartate aminotransferase (AST), thereby lowered liver damage. Dietary ETSP may suppress fatty acid transport and lipid synthesis, and promote lipid catabolism by activating FGF21/AMPK pathway. Finally, quadratic regression analysis of the specific growth rate (SGR) revealed that the optimal dietary ETSP level for largemouth bass was 40.0 g/kg.